Human Papillomavirus infection and cervical lesions in HIV infected women on antiretroviral treatment in Thailand. Issue 5 (May 2017) - ,; Zarca, Kevin; Brunet-Possenti, Florence; Blake, Alexandre; Althaus, Thomas; Gallot, Céline; Desbiolles, Alice; Fayard, Florence; Dib, Fadia; Le Pluart, Diane; Proute, Myrtille; Tiv, Métrey; et al.
Summary: Objectives: To estimate the prevalence and factors associated with Human Papillomavirus (HPV) infection, HPV genotypes and cytological/histological high-grade (HSIL+/CIN2+) lesions. Methods: We conducted a cross-sectional study within a prospective cohort of HIV-infected women on combination antiretroviral therapy (cART). Cervical specimens were collected for cytology and HPV genotyping (Papillocheck ® ). Any women with High-Risk-HPV (HR-HPV), and/or potentially HR-HPV (pHR-HPV) and/or ASC-US or higher (ASC-US+) lesions were referred for colposcopy. Factors associated with HR-HPV infection and with HSIL+/CIN2+ lesions were investigated using mixed-effects logistic regression models. Results: 829 women were enrolled: median age 40.4 years, on cART for a median of 6.9 years, median CD4 cell-count 536 cells/mm3, and 788 (96%) with HIV-viral load<50copies/mL. Of 214 (26%) infected with HPV: 159 (19%) had ≥1 HR-HPV, of whom 38 (5%) HPV52, 22 (3%) HPV16, 9 (1%) HPV18; 21 (3%) had pHR-HPV, 34 (4%) low risk-HPV infection, and 56 (26%) had multiple genotypes. Younger age, low CD4 cell-counts and low education were independently associated with HR-HPV infection. 72 women (9%) had ASC-US+ and 28 (3%) HSIL+/CIN2+ lesions. HR-HPV infection was independently associated with HSIL+/CIN2+ lesions. Conclusion: The prevalence of HPV infection and of cervical lesions was low. The HPV genotype distribution supports the use of 9-valent vaccine in Thailand. Graphical abstract: Highlights: The prevalence of HPV52 was 5%, HPV39 3%, HPV51 3%, HPV16 3%, and HPV18 1%. The prevalence of HR-HPV infection was 19%. The prevalence of HSIL+/CIN2+ lesions was 3%. Younger age, low CD4 count ands low education were associated with HR-HPV infection. The risk of HSIL+/CIN2+ lesions was 9 times higher in women with HR-HPV infection.